Fatty acid and mineral contents of Lycium ruthenicum Murr. and antioxidant activity against isoproterenol‐induced acute myocardial ischemia in mice. Issue 2 (7th January 2020) - Yossa Nzeuwa, Irma Belinda; Xia, Hui; Shi, Yuanyuan; Yang, Chao; Shah, Muhammad Waseem; Guo, Baofu; Wang, Liya; Sun, Guiju
Abstract: Dried fruits of black goji were investigated for their fatty acid, mineral contents, and antioxidant activity against isoproterenol‐induced acute myocardial ischemia in mice was revealed. It was observed that the key fatty acids from Lycium ruthenicum Murr. (LRM) oil studied included linoleic (59.38%), oleic (20.85%), palmitic (7.07%), linolenic (2.98%), and stearic acids (5.31%), which together comprised 95.59% of the total fatty acids. The key mineral nutrients studied were potassium (17, 631.15 mg/kg), calcium (2004.4 mg/kg), and magnesium (1, 274.6 mg/kg), while copper, iron, manganese, and zinc were found in trace. Moreover, oral administration of water extraction of LRM exhibited significant reduction of enzyme activities, and MDA level triggered by ISO to be near normal level, while exhibited a significant increase of SOD and GSH activities. Our results provide deep insight on LRM as a potential source of high‐value phytochemicals for the development of new functional food and beverage products. Abstract : Lycium ruthenicum nutrient content not determined yet including mineral and fatty acid was investigated. The whole crude water extract was also investigated for its antioxidant activity against acute myocardial ischemia in mice.